Germany's value-based partnerships in the Indo-Pacific - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2024)
Diversifying Germany's bilateral partnerships in the Indo-Pacific is one of the central goals of German policy. On the one hand, this diversification aims to reduce economic dependence on China, and on the other - in the context of systemic rivalry with authoritarian states - to bring about cooperation with states that share common values with Germany, so-called Wertepartnern (value-based partners). However, it is not clearly defined which values are fundamental to value-based partnerships. It also remains unclear which states in the Indo-Pacific are referred to as value-based partners and how these value-based partnerships differ from "normal" bilateral relations with other states in the region. Instead, this study shows that the significance that is rhetorically attached to cooperation with value-based partners is at odds with the vague concept of "value-based partnership" and its limited importance as a basis for bilateral cooperation. A comparison of value-based partners with a control group of non-value-based partners across different policy areas produces mixed results. The assumed correlation between being categorised as a value-based partner and closer international cooperation based on shared norms and values cannot, with any coherence, be demonstrated empirically. A comprehensive revision of the hitherto diffuse concept of value-based partnerships is recommended - either by normative sharpening, combined with a narrowing of the circle of states designated as value-based partners, or by eradicating the term from the political vocabulary.
Keywords: 320; Germany; value-based partnerships; Indo-Pacific; Singapore; Australia; Japan; South Korea; New Zealand